Loeys-Dietz syndrome - Bogumiła Wójcik-Niklewska; Erita Filipek (Klinika Oczna)
Loeys-Dietz syndrome is a rare syndrome of genetically determined congenital defects characterized by specific dysmorphic features, vascular tortuosity, aneurysms, mitral valve disease, and bone abnormalities. Eye disorders include lens subluxation, myopia, retinal detachment, and the bluish colour of eye whites. To present a case of a child with ocular manifestations of Loeys-Dietz syndrome. A 6-year-old boy with Loeys-Dietz syndrome, confirmed by molecular genetic testing, presented with high myopia, subluxated lenses, dysmorphic features, and disorders of the osteoarticular and cardiovascular systems. The boy underwent a complete ophthalmic examination, ocular ultrasound (US), ultrasound biomicroscopy (UBM), electrophysiological assessment (flash VEP), and magnetic resonance imaging (MRI) of the orbits. The examinations revealed lens subluxation in both eyes resulting from congenital anomalies in the lenses, ligamentous apparatus, and ciliary body. Ultrasound demonstrated numerous linear preretinal echoes. Intraocular pressure was normal, i.e., 14 mmHg in the right and 15 mmHg in the left eye. The best-corrected visual acuity was 0.01 in the right and 0.3 in the left eye, respectively. Refractometry showed –23.0 D in the right and –21.75 D in the left eye. The patient had abnormal flash VEP. Due to a significant lens subluxation, a decision was made to perform pars plana lensectomy combined with anterior vitrectomy. Children with genetically determined congenital syndromes should be constantly monitored by an ophthalmologist for a thorough evaluation of the eyes and a prognosis of the development of visual function.